AYURVEDIC MEASURES OF IMMUNIZATION IN CHILDREN - Singh, Jyoti; Laxmi (International Research Journal of Ayurveda & Yoga, 2024)
Immunity is the state of having sufficient biological defences to avoid infection, disease or other unwanted biological invasion. It is the capability of the body to resist harmful from entering it. A healthy immune system is vital for children as they exposed to a plethora of germs. Many micro-organism enter the body through air and water, but fails to create disease due to immune response present in the body. Many children prone to disease due to change in climate, on the other hand some children remain healthy in spite of change in climate and do not get affected by any disease. The most important thing in relation to health and disease is immunity. Concept of Vyadhikshamatva described in the classical text of Ayurveda is all about immunity. Rasayana therapy, Lehana karma and many more Ayurvedic preparation are helpful in enhancing the child immunity.